Little Miss Dotty - Hargreaves, Roger (World international Limited, 1984)
Little Miss Dotty is the 17th book in the Little Miss series. Little Miss Dotty is just plain dotty. She lives in Nonsenseland (where Mr. Silly and Mr. Nonsense live).
Keywords: Juvenile Fiction-Book